Comprehensive identification of chemical fingerprint and potential quality markers of leaves and roots of two Aloe species via LC–MS/MS and computational analyses in relation to anti-virulence activity - Passent M. Abdel-Baki; Rana M. Ibrahim; Mai E. Hussein; Mohammed Abu-Elghait; Mona Shaban E. M. Badawy; Maha Hanafi; Mansour Sobeh; Nariman E. Mahdy (Future Journal of Pharmaceutical Sciences)
Abstract Background Over the past centuries, Aloe species have been traditionally used in managements of infectious ailments. However, no scientific investigation has been conducted into their mechanistic actions behind their antimicrobial activities. The main purpose of this study is to investigate the anti-virulence activities of Aloe marlothii A. Berger (AM) and Aloe striata Haw (AS) leaves and roots against Pseudomonas aeruginosa based on biofilm, pyocyanin and motility assays. Besides, the metabolic profiling of their different organs was evaluated via HPLC–MS/MS analysis. A molecular docking study of marker compounds into a LasR target was conducted to gain an insight into the bioactive metabolites involved into mechanism of action. Results A. marlothii roots (AMR) and A. striata leaves (ASL) displayed significant activity against P. aeruginosa at 0.5 MIC via decreasing the biofilm development, pyocyanin production, swarming and swimming motilities. HPLC–MS/MS analysis led to the identification of one hundred metabolites belonging to different chemical classes. Additionally, it revealed the richness of AMR and ASL with anthraquinones and anthrones. Molecular docking of tentatively identified anthraquinones and anthrones was performed, revealing that chrysophanol-8-O-glucoside and 6-malonylnataloin revealed superior binding affinities and stabilities within the pocket of LasR system, compared to TP-4. Conclusions These findings give sound evidence for the use of AMR and ASL as effective anti-virulence agents against P. aeruginosa.